1997
DOI: 10.1097/00007435-199704000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Markers in Men Seeking Human Immunodeficiency Virus Antibody Testing in Mexico City

Abstract: These data demonstrate that coinfection with HBV is common in the HIV-positive men studied. The highest prevalences of HBsAg and anti-HBc were observed among homosexual men. These results highlight the need to intensify safe-sex education campaigns and to promote hepatitis B vaccination especially among this population group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
1
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
2
7
1
4
Order By: Relevance
“…Other studies in Europe reported higher prevalence in these individuals (Ockenga et al 1997, Denis et al 1997. A recent study in men infected with HIV in Mexico City found a similar prevalence of HBV serological markers to that reported in this paper (Juarez-Figueroa et al 1997).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Other studies in Europe reported higher prevalence in these individuals (Ockenga et al 1997, Denis et al 1997. A recent study in men infected with HIV in Mexico City found a similar prevalence of HBV serological markers to that reported in this paper (Juarez-Figueroa et al 1997).…”
supporting
confidence: 90%
“…Male homosexuality has been reported amongst the main risk factors for the coexistence of HIV and HBV infections (Juarez-Figueroa 1997). In Cuba, homoxesuals men constitute 64.5% of all male individuals with HIV/Aids infection (Pérez et al 1996).…”
mentioning
confidence: 99%
“…The groups described are similar in many ways to other populations with bisexual behavior, but heterosexual identities, found both in Latin America (Cáceres & Rosasco, 2000;Finlinson, Colon, Robles, & Soto, 2006;Juarez-Figueroa et al, 1997;Kerr-Pontes, Gondim, Mota, Martins, & Wypij, 1999;Tabet et al, 2002;Tabet et al, 1996) and in the United States (Chu, Peterman, Doll, Buehler, & Curran, 1992;Diaz, 1998;Juarez-Figueroa et al, 1997;Kerr-Pontes et al, 1999;Tabet et al, 2002;Tabet et al, 1996). The esquineros also report substantial rates of compensated sex, which from previous ethnographic work appears to occur primarily with men (Salazar et al, 2005) likening some of the men in this population to "hustlers" described in the United States (Rietmeijer, Wolitski, Fishbein, Corby, & Cohn, 1998;Simon, Morse, Balson, Osofsky, & Gaumer, 1993;Sullivan, 1996).…”
Section: Discussionsupporting
confidence: 61%
“…14 The UNAIDS 2012 report estimated a prevalence of HIV infection of 17% among MSM in Mexico. 15 However, a HIV prevalence of 30% and even 40% among MSM in Mexico City has been reported after 1988. 16 More recently, a study that reported HIV prevalence among MSM in 24 cities across Mexico found a global frequency of 16.9% with fluctuations according to the distribution of the cities in five regions: the CentralEast region had the highest HIV frequency (20.4%) and the Central-West region had the lowest (9.9%).…”
Section: Hiv/aids Program Of Mexico Citymentioning
confidence: 99%